Inflammatory signalling pathways involved in astroglial activation by unconjugated bilirubin - Fernandes, A (2015)
During neonatal hyperbilirubinaemia, astrocytes activated by unconjugated bilirubin (UCB) may contibute to brain toxicity through the production of cytokines. As a first step in addressing the signal transduction cascades involved in the UCB-induced astro